PENGARUH KOMPETENSI PROFESIONAL DAN KOMPETENSI KEPRIBADIAN TERHADAP KINERJA GURU - Sopandi, Andi (Sekolah Menengah Kejuruan (SMK) Pustek, 2019)
Bad behavior of students is one proof of educational failure, and the teacher is the person who most responsible. Therefore, the school must care about teacher performance, with all efforts and capital. This study aims to analyze teacher performance factors. Quantitative is used as a research method, the object of research is MTs Ma'arif Cipakem Kuningan, the study sample was 75 teachers, the sample technique using census, the research instrument is questionnaire, and linear regression is used as an analysis method. The results showed those professional competence and personality has significant effect on teacher performance. This finding confirms that performance is the result of intellectual and emotional ability, so the reflection is correct teaching